2009
DOI: 10.1007/s11104-009-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertilizer and spatial heterogeneity in soil pH on microbial biomass indices in a long-term field trial of organic agriculture

Abstract: In the Darmstadt long-term fertilization trial, the application of composted cattle farmyard manure without (CM) and with (CMBD) biodynamic preparations was compared to mineral fertilization with straw return (MIN). The present study was conducted to investigate the effects of spatial variability, especially of soil pH in these three treatments, on soil organic matter and soil microbial biomass (C, N, P, S), activity (basal CO 2 production and O 2 consumption), and fungal colonization (ergosterol). Soil pH was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 62 publications
6
60
2
3
Order By: Relevance
“…The application of manure in the present experiment-in contrast to the stockless experiment described by Emmerling 25 , which was also conducted under organic farming conditions with a ley-based crop rotation-may have been a crucial factor in the dynamics of the microbial populations. Heinze et al 54 found enhanced microbial biomass as a result of application of manure.…”
Section: Soil Microbial Biomass and Activitymentioning
confidence: 99%
“…The application of manure in the present experiment-in contrast to the stockless experiment described by Emmerling 25 , which was also conducted under organic farming conditions with a ley-based crop rotation-may have been a crucial factor in the dynamics of the microbial populations. Heinze et al 54 found enhanced microbial biomass as a result of application of manure.…”
Section: Soil Microbial Biomass and Activitymentioning
confidence: 99%
“…Thus, pH has an important effect on microbial populations, especially on bacteria, which reduce their growth rates, biomass, and diversity as pH decreases (Rousk et al, 2009). Farm 2 and F3 had lower pH values than F1, probably because of their higher inputs of inorganic fertilizers (Table 1) (Heinze et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The negative effects of fertilization may have been caused by direct toxicity and changes in pH due to ammonium-based fertilizers. According to Heinze et al [36], the application of mineral fertilizers resulted in a significantly decreased soil pH, which is an important regulator of the development of soil microorganisms because it affects the solubility of various mineral substances, simultaneously influencing their absorbability. Therefore, the pH value ( Fig.…”
Section: Soil Microorganismsmentioning
confidence: 99%